"/ ---/ in der Dünung / wandernder Worte." - Božič, Andrej (Primerjalna književnost, 2013)
I discuss the context of literary history in Paul Celans poetry, focusing on the role and status of quotation as a sign of the reception of the historicity of literature, its traditions, and its contemporaneity. Within the development of Celans poetic oeuvre, I especially accentuate the confrontation with the fate and poetry of Osip Mandelstam.
Keywords: Celan, Paul, 1920-1970; Mandelštam, Osip, 1891-1938; nemška poezija; avtopoetika; citat; citatnost; ruska poezija; Judaism; judovstvo